2005
DOI: 10.1007/s00440-004-0408-1
|View full text |Cite
|
Sign up to set email alerts
|

Aging in two-dimensional Bouchaud's model

Abstract: Let E x be a collection of i.i.d. exponential random variables. Symmetric Bouchaud's model on Z 2 is a Markov chain X(t) whose transition rates are given by w xy = ν exp(−βE x ) if x, y are neighbours in Z 2 . We study the behaviour of two correlation functions: P[X(t w + t) = X(t w )] and P X(t ) = X(t w )∀t ∈ [t w , t w + t] . We prove the (sub)aging behaviour of these functions when β > 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 10 publications
2
65
0
Order By: Relevance
“…The scaling limit is a singular diffusion now known under the name of FIN. In higher dimension d ≥ 2, the scaling limit is known to be the so called Fractional Kinetics process: d-dimensional Brownian motion time changed by the inverse of an independent stable subordinator as proved in [16], [9] and [7], the strategy being similar to [8]. Besides a number of estimates on the Green kernel of simple symmetric random walk in Z d , the proof in the d = 2 case involves rather sophisticated renormalization technics.…”
Section: Remarkmentioning
confidence: 99%
See 2 more Smart Citations
“…The scaling limit is a singular diffusion now known under the name of FIN. In higher dimension d ≥ 2, the scaling limit is known to be the so called Fractional Kinetics process: d-dimensional Brownian motion time changed by the inverse of an independent stable subordinator as proved in [16], [9] and [7], the strategy being similar to [8]. Besides a number of estimates on the Green kernel of simple symmetric random walk in Z d , the proof in the d = 2 case involves rather sophisticated renormalization technics.…”
Section: Remarkmentioning
confidence: 99%
“…As far as trap models on Z d are concerned, excluding the asymmetric case (where π depends on τ in a specific way, as mentioned above; see [1], [17], [6], [25]), only the case of the simple symmetric random walk was investigated so far. It corresponds to π being the uniform law on the nearest neighbors of the origin.…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us make a comment about the meaning of the conditional probabilities P(A 0 |l(τ −n 1/(1+α) , 0) = y) appearing in (7). One can use any regular version of the conditional probabilities of (l(τ −n 1/(1+α) , u)) u≥0 given l(τ −n 1/(1+α) , 0) to define the function y → P(A 0 |l(τ −n 1/(1+α) , 0) = y) up to a set of ν 0 -measure zero.…”
Section: Strategy Of the Proofmentioning
confidence: 99%
“…the BTM has a behavior completely different from the one-dimensional case, as shown by Ben Arous andČerný in [5], and by Ben Arous,Černý and Mountford in [7] (see also [17]). In these papers it is shown that the scaling limit of the BTM on For an spectral characterization of aging see [10].…”
Section: Introductionmentioning
confidence: 99%